Strategy of civic education teachers in building student social character to maintain local culture in the society 5.0 era - Pipit Widiatmaka; Asep Wibowo; Arief Adi Purwoko (Universitas Tanjungpura, 2023)
The era of Society 5.0 is synonymous with internet technology that makes it easier for teachers to build social character, but it turns out that this era hurts student character development, namely, students experience a social character crisis, so many are anti-social and leave the local culture. The objectives of the study were to 1) determine the meaning of social character in the life of the nation and state, 2) examine the role of Civic Education in maintaining local culture in the era of society 5.0, and 3) examine teacher strategies in building social character in students in the era of society 5.0. This research uses a qualitative approach with descriptive research methods, so data collection techniques use interviews, observations, and document studies. The informants in this study were two teachers; observations were made of the Civic Education learning process and the behavior of students while at MTs N 4 Klaten through the study of syllabus documents and RPP. The data analysis technique used is interactive data analysis. The results showed that the meaning of social character in the life of the nation and state is to establish harmony between differences and maintain harmony between the state and citizens for the realization of unity and unity. In the era of society 5.0, maintaining local culture is very important, namely by educating and inspiring students to maintain and preserve the local wisdom that develops in their respective regions and wisely use internet technology so that it is not easily influenced by values or cultures from outside, especially those that conflict with the personality of the nation. The teacher's strategy in building social character in the era of Society 5.0 is by example, maintaining discipline and habituation, and creating a comfortable and conducive school culture. In addition, there are also supporting activities, namely social service, protecting the environment, and providing compensation to poor and orphaned children